Pharmacovigilance study on neurological adverse reactions of proteasome inhibitors in the FDA adverse event reporting system - Li, Shuyue; Ling, Tao; Liu, Yan; Li, Jun (Frontiers in Pharmacology, 2026)
ObjectiveBortezomib, carfilzomib and ixazomib are the proteasome inhibitors (PIs) used to treat multiple myeloma (MM). We conducted a comprehensive pharmacovigilance analysis of their neurotoxicity using the Food and Drug Administration Adverse Event Reporting System (FAERS), including not only peripheral neurotoxicity but also central neurotoxicity, to provide reference for safe and rational clinical use.MethodsWe obtained PIs’ adverse reaction reports during Q1 2004 to Q2 2025 from the FAERS database. Adverse drug event (ADE) signals of bortezomib, carfilzomib and ixazomib were analyzed by statistical methods including Reporting Odds Ratio (ROR), Proportional Reporting Ratios (PRR), Bayesian Confidence Propagation Neural Network (BCPNN) and Multi-item Gamma-Poisson Shrinker (MGPS). ADEs sorted by frequency of occurrence and signal strength. Subgroup analyses based on gender was performed to explore differences. Time-to-onset profiles were analyzed using the Weibull Shape Parameter (WSP) test.ResultsA total of 33,322, 14,063, and 16,562 ADEs of bortezomib, carfilzomib and ixazomib were analyzed, respectively from the FAERS database. The most common neurological adverse reaction signals for bortezomib, carfilzomib, and ixazomib are peripheral neuropathy (PN), with bortezomib having the highest number of reports (n = 2,681). Analysis shows that compared to the other two drugs, bortezomib exhibits higher signal intensity in neurological adverse events. The most prominent signal of bortezomib is autonomic neuropathy [n = 96; ROR 70.16 (95% CI 56.79–86.67)]. The strongest signal of carfilzomib is in hypertensive cephalopathy [n = 7; ROR 18.09 (95% CI 8.58–38.12)], while ixazomib has the highest signal in burning feet syndrome [n = 3; ROR 16.61 (95% CI 5.32–51.91)]. The median to onset time for neurological adverse events related to bortezomib, carfilzomib, and ixazomib were 33days (IQR 13–91), 35 days (IQR 9–145), and 80 days (IQR 19–251), respectively.ConclusionIn real-world pharmacovigilance studies, the peripheral neurotoxicity of carfilzomib and ixazomib was lower than that of bortezomib. In addition to PN, it is necessary to pay more attention to the special central neurological adverse events of PIs, such as posterior reversible encephalopathy syndrome (PRES) related to bortezomib and carfilzomib, and hypertensive encephalopathy related to carfilzomib, for early symptom identification and diagnosis. For ixazomib, attention should also be paid to neuromuscular symptoms and prevention of neuralgia caused by herpes zoster virus.